Internal Acoustic Canal Stenosis Due to Hyperostosis - Goodarzi, Amir; Toussi, Atrin; Garza, Nicholas; Lechpammer, Mirna; Brodie, Hilary; Diaz, Rodney C.; Shahlaie, Kiarash (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Exostoses and osteomas are benign, insidious lesions of the bone involving the internal acoustic canal (IAC). We present two cases of IAC exostoses managed with surgical decompression and review the clinical outcomes of previously reported cases in the literature.Methods A comprehensive search was conducted using PubMed Central, Web of Science Core Collection, and Google Scholar databases to identify previous reports of IAC exostoses and osteomas. A total of 26 reported cases were identified, and patient presenting symptoms, management strategies, and response to surgery was obtained when available.Results Of the 13 patients who underwent surgical decompression, 8 patients had resolution of vertigo symptoms, 10 patients had improvement of tinnitus symptoms, and all patients maintained some level of serviceable hearing.Conclusion IAC exostoses and osteomas are rare lesions that lead to insidious onset of debilitating symptoms from vestibulocochlear nerve dysfunction. Although the role of surgical decompression remains unclear, it appears that patients presenting with vertigo have more favorable response to surgical decompression as compared with those presenting with tinnitus and sensorineural hearing loss.
Keywords: internal acoustic canal; osteoma; exostosis; decompression; surgical